Analysis Of The Relationship Between Self-Concept And Self-Esteem And The Behavior Of Female Students In Reproductive Health Maintenanceat The District Islamic Boarding School Batanghari Multicenter Study - Sari, Puspita; Sri Astuti Siregar; Nasution, Helmi Suryani; Budi Aswin (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Reproductive health is a serious problem throughout human life. Vaginal discharge is one of the reproductive health problems of adolescents, especially one that women often complain about. Survey results show that 65% of teenage girls in Indonesia experience vaginal discharge. Self-esteem is an important component in forming a person's self-concept, where self-concept is an important thing in determining a person's behavior, including maintaining reproductive health. This research aims to determine the relationship between self-concept and self-esteem and the behavior of female students in maintaining reproductive health in Islamic boarding schools in Batanghari Regency. This research is a correlative descriptive quantitative research with a cross-sectional, multi-centre research design involving 3 Islamic boarding schools in Batanghari Regency. Sampling used random sampling. The total sample was 98 respondents. The data analysis used includes univariate analysis (respondent characteristics, self-concept, self-esteem, student behavior), as well as bivariate analysis to measure the relationship between self-concept and self-esteem. The results of the research showed that 63.3% of respondents had poor female student behavior in maintaining reproductive health. There is a relationship between self-concept (p-value: 0.008), Self-Esteem (p-value: 0.006) and the behavior of female students in maintaining reproductive health. The research results showed that of the 56 respondents with a negative self-concept, 44 (74.6%) respondents had poor behavior among female students in maintaining reproductive health. Of the 39 respondents with positive self-concept, 18 (46.2%) respondents had good female behavior in maintaining reproductive health. Efforts are needed from Islamic boarding schools to conduct training and health promotion for female students in maintaining reproductive health regarding self-concept and self-esteem.